Ontology-based information retrieval for historical documents - Fatihah, Ramli; Shahrul Azman, Mohd Noah; Tri Basuki, Kurniawan (Institute of Electrical and Electronics Engineers Inc., 2017)
This article presents an ontology-based approach to designing and developing new representation IR system instead of conventional keyword-based approach. Such representation improves the precision and recall of document retrieval. Experiments carried out on the ontology-based approach and keyword-based approach demonstrates the effectiveness of the proposed approach.